Early Gray Matter Volume Loss in MAPT H1H1 de Novo PD Patients: A Possible Association With Cognitive Decline - Sampedro, Frederic; Marín-Lahoz, Juan; Martínez-Horta, Saul; Pagonabarraga, Javier; Kulisevsky, Jaime (Frontiers in Neurology, 2018)
The MAPT H1 haplotype has been identified as a predictor of cognitive decline in Parkinson’s disease (PD). However, its underlying pathological mechanisms have not been fully established. In this work, using a cohort of 120 de novo PD patients with preserved cognition from the Parkinson's Progression Markers Initiative (PPMI) database, we found that patients who were homozygous for MAPT H1 had less gray matter volume (GMV) and greater one-year GMV loss than patients without this genetic profile. Importantly, these changes were associated with a longitudinal worsening of cognitive indicators. Our findings suggest that early GMV loss in MAPT H1H1 PD patients increases their risk to develop cognitive decline.